Mineral Contents and Fatty Acids Compositions of Fillets of Female and Male Pangas (Pangasıus Hypophthalmus, Sauvage 1878) Cultured in Turkey - Artar, Engin; Olgunoglu, Mine Percin; Olgunoglu, İlkan Ali (Progress in Nutrition, 2022)
Pangas (Pangasius hypophthalmus) is a food resource with great economical importance in Asian countries. This study provides baseline data on some macro and micro minerals and fatty acids composition in fillets of female and male Pangasius hypophthalmus cultured in Turkey. Among the minerals determined in both fillets samples, Na was found to be highest, followed by K, Mg and Ca. The order of average micro minerals concentrations was Fe>Zn>Cu>Mn in both fillet samples. In the research, statistically significant differences were not observed in all determined macro and micro minerals when compared to each other. The major fatty acids detected were C16:0, C18:0, C18:1(n-9) and C18:2 (n-6). The results revealed that fillets of male pangas are a better source of minerals, protein and fatty acids than fillets from female pangas.